OSTEOKONDROMA OF DISTALIS ULNAR WITH MASADA TIPE I DEFORMITY AMONG SEVEN YEARS OLD BOY: A CASE REPORT - Putu Gede Thurdy Gustandra (E-Jurnal Medika Udayana, 2014)
Osteokondroma a benign tumor on the spine of the most common and manifests as asolitary non - hereditary exostosis is the long bone metaphysis in the majority of cases.Pain, impaired joint motion, tendon inflammation, as well as the compression of bloodvessels and peripheral nerves is a complication caused by osteokondroma. Deformity isa frequent complication reported in osteokondroma that the bones of the lower arm(forearm). This report discusses the distal ulna osteokondroma on a male patient aged 7years with shortening deformity of the ulna ( ulnar shortening ) according to theclassification of type I. Masada Surgery ( excision of the tumor ) is the primarytreatment option in this case . Forearm deformity subsequently corrected through theinstallation procedure with the ulnar lengthening plate fixation. Correction of thedeformity provides improved cosmetic appearance of the forearm after surgery in thesepatients.